EDUKASI PENYAKIT KULIT, PERILAKU HIDUP BERSIH, DAN CUCI TANGAN PAKAI SABUN UNTUK SANTRI PONDOK PESANTREN MODERN ASSA’ADAH SERANG BANTEN - Yudhi Nugraha; Maria Silvester Thadeus; Nasihin Saud Irsyad (MADANI: Jurnal Pengabdian Kepada Masyarakat, 2021)
Skin infection case is still highly found in Indonesia with prevalence at 4.6-12.95%. The highest prevalence rate was found in the pesantren. The skin infection disease that often observed in students that lives in pesantren mainly Scabies. The prevalence of scabies in pesantren found more than 43%. This shows that the spread of skin diseases in the pesantren is still high. Actually, this coundation that caused by a microorganism infection is can be prevented easily. Hand hygiene is of utmost concern to everyone and is the earliest and most effective method of preventing the transmission of health-related pathogenic microbes. Efforts to keep hands clean is one important step to prevent disease and prevent disease transmission to others. This activity is carried out through counseling using the lecture method through the help of video media and leaflets. After that, a demonstration of how to wash hands with soap was carried out through six steps, which were then followed by all activity participants who were students in the Assaaadah Islamic Boarding School, Serang Banten Regency. This activity was successfully carried out even though in a pandemic condition that caused the boarding school to be closed completely to visitors, but with these limitations, an online approach was made to carry out the activity. The results of the activity show that 50 students of the modern Assaadah Islamic boarding school have understood the importance of washing hands with soap, the theory scabies, and the principles of clean living in a communal environment.